2018
DOI: 10.1364/boe.9.001006
|View full text |Cite
|
Sign up to set email alerts
|

Household light source for potent photo-dynamic antimicrobial effect and wound healing in an infective animal model

Abstract: Photodynamic antimicrobial chemotherapy (PACT) is considered a promising alternative to conventional antibiotic approach. We have previously developed a novel PS containing five lysine amino acids, pentalysine-β-carbonylphthalocyanine Zinc (ZnPc(Lys)), which in the presence of light, is highly toxic against a range of bacterial strains, including hospital isolated, drug resistant Acinetobacter baumannii. Here, we study the effect of light fluence of the two light sources on the PACT potency of ZnPc(Lys). We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It should also not be effluxed out by the microbial efflux systems (Cieplik et al, 2018; Hu et al, 2018; Tomb et al, 2018; Wozniak and Grinholc, 2018). Efficacy of aPDT also depends on the light fluence, PS concentration and treatment time (Tomb et al, 2017; Sueoka et al, 2018; Ullah et al, 2018).…”
Section: Photodynamic Light Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It should also not be effluxed out by the microbial efflux systems (Cieplik et al, 2018; Hu et al, 2018; Tomb et al, 2018; Wozniak and Grinholc, 2018). Efficacy of aPDT also depends on the light fluence, PS concentration and treatment time (Tomb et al, 2017; Sueoka et al, 2018; Ullah et al, 2018).…”
Section: Photodynamic Light Therapymentioning
confidence: 99%
“…Notably, it was also shown that this combination was non-toxic to human keratinocytes. Conjugates such as ZnPc(Lys) 5 (a zinc phthalocyanine derivative coupled with pentalysine) also showed a synergistic antibacterial action which was sufficient to heal S. aureus wound infection in mice models (Ullah et al, 2018).…”
Section: Photodynamic Light Therapymentioning
confidence: 99%
“…[8][9][10] To sort out their inherent insolubility in aqueous media, these chromophores can be endowed with hydrophilic groups; [11][12][13][14][15][16][17] in particular, functionalization with positively charged moieties imparts water-solubility to the Pcs and makes them potential PS in PDI. [18][19][20] However, owing to their extended π-conjugation, Pcs exhibit a high aggregation tendency in aqueous media, forming oligomers in solution that can be either photoactive (i.e. J-type aggregates), [21] or present cancelled 1 O2 generation abilities.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli (ATCC 8739), S. aureus (ATCC 6538), and MRSA (ATCC 33591) were acquired from ATCC. Bioluminescent strains of E. coli DH5α were constructed by transformation of plasmid pAKlux2.1, which contained a complete bacterial luciferase operon as described (Ullah et al, 2018;Chen et al, 2019), and S. aureus Xen29 (NCTC8532) containing a stable copy of the modified Photorhabdus luminescens luxABCDE operon was purchased from Shanghai Biofeng Company.…”
Section: Methodsmentioning
confidence: 99%